Mitomycin C in the endoscopic treatment of tracheal stenosis: A prospective cohort study - Cataneo, Daniele Cristina [UNESP] (2018)
Objective: To evaluate the efficacy of mitomycin C (MMC) in the endoscopic treatment of tracheal stenosis. Methods: Patients with laryngotracheal, tracheal, or tracheobronchial stenosis were treated with dilation and topical MMC. The inclusion criteria were as follows: being ineligible for surgery (for medical reasons) at the time of evaluation; membranous stenosis responding well to dilation; and postoperative stenosis at the anastomosis site. Etiology of stenosis and indication for treatment with MMC, as well as site, length, and percentage of stenosis, together with presence of tracheostomy and duration of follow-up, were analyzed. The outcomes evaluated were symptom-free interval ≥ 12 months, number of dilations with topical application of MMC, and complications. Results: Twenty-two patients (15 men and 7 women) were treated between 2003 and 2010. Stenosis was due to endotracheal intubation in 15 patients and surgery in 8. Pure tracheal stenosis was encountered in 13 patients, subglottic stenosis was encountered in 4, tracheobronchial stenosis was encountered in 3, and complex stenosis was encountered in 2. The length of stenosis ranged from 0.5 cm to 2.5 cm, and the percentage of stenosis ranged from 40% to 100%. Nine patients had undergone tracheostomy and had a Montgomery T-tube in situ. Treatment was successful in 14 patients, who remained free of symptoms for at least 12 months. The number of topical applications of MMC ranged from 1 to 5, and complications included fungal infection, keloid scarring, granuloma, and mediastinal emphysema. Conclusions: MMC appears to be effective in the endoscopic treatment of tracheal stenosis.